Rotavirus Immunization and Stunting Among Indonesian Children Under Five: A Cross-Sectional Analysis of the 2024 Indonesian Nutritional Status Survey (SSGI) - Fitria, Fitria; Anggondowati, Trisari; Anggraini, Sely; Putri, Nadia (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2026)
Introduction: Stunting remains a major public health problem in Indonesia. Rotavirus-related diarrhea can impair child growth through recurrent infections, nutrient malabsorption, and increased susceptibility to undernutrition, thereby increasing the risk of stunting. This study aimed to examine the association between rotavirus immunization status and stunting among children under five years of age in Indonesia in 2024. Methods: A cross-sectional study was conducted using data from the 2024 Indonesian Nutritional Status Survey (SSGI), including 243,322 children aged 4–59 months. Data were analyzed using a causal model approach. Cox regression with constant time was employed to estimate adjusted prevalence ratios (aPRs) and 95% confidence intervals (CIs). Results: Children who did not receive complete rotavirus immunization had a higher prevalence of stunting (aPR = 1.09; 95% CI: 0.99–1.20), whereas children who did not receive any rotavirus immunization had a 1.31-fold higher prevalence of stunting (95% CI: 1.23–1.40) compared with children who received complete rotavirus immunization. Conclusion: Children who did not receive rotavirus immunization had a higher prevalence of stunting than those who received complete rotavirus immunization. Expanding rotavirus immunization coverage should be considered an important component of strategies to accelerate stunting reduction in Indonesia.